2020
DOI: 10.5888/pcd17.190373
|View full text |Cite
|
Sign up to set email alerts
|

Wellness School Assessment Tool Version 3.0: An Updated Quantitative Measure of Written School Wellness Policies

Abstract: Schools play an important role in promoting student wellness. As directed by the Healthy Hunger-Free Kids Act, the US Department of Agriculture updated the requirements for written school wellness policies in 2016. The WellSAT (Wellness School Assessment Tool) is an online tool that provides a quantitative score for wellness policy comprehensiveness and strength. The WellSAT has been updated 3 times over the past decade to remain current with federal law and best practices. In this article, we describe the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…We found that policy language was present for 40% to 79% of items in each newly added domain. These comprehensiveness scores were roughly similar to those found in the development of the WellSAT 3.0, 9 suggesting that the WellSAT WSCC assessment of the new domains is similar to that of the more established WellSAT 3.0 measure. In addition, we found strong policy language for around 30% to 65% of items in each new domain.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We found that policy language was present for 40% to 79% of items in each newly added domain. These comprehensiveness scores were roughly similar to those found in the development of the WellSAT 3.0, 9 suggesting that the WellSAT WSCC assessment of the new domains is similar to that of the more established WellSAT 3.0 measure. In addition, we found strong policy language for around 30% to 65% of items in each new domain.…”
Section: Discussionsupporting
confidence: 71%
“…The WellSAT WSCC expands upon the WellSAT 3.0, a third-generation measure that primarily assesses how well local SWPs address the Nutrition Environment and Services and Physical Education and Physical Activity domains, as well as additional elements of wellness promotion and evaluation. 8,9 The WellSAT WSCC adds 8 subscales that correspond to additional WSCC domains: Health Education, Social and Emotional Climate, Safe Environment, Health Services, Behavioral Supports, Employee Wellness, Community Involvement, and Family Engagement. It also expands the WellSAT 3.0's evaluation subscale to encompass a comprehensive school health approach.…”
Section: The Role Of Policymentioning
confidence: 99%
“…For example, a study of 130 districts in VA found that locally-developed LWPs were both stronger and more comprehensive than policies based on templates from a state board, particularly for topics of LWP communication and promotion, and evaluation of the LWP; however, policies from both sources tended to be weak and lacking comprehensiveness [ 41 ]. Recent work in 2019 examined language in model wellness policies that had been issued by 34 states across the US [ 42 ], and found that, overall, the strength of the language for RME provisions was relatively low, with an average score of 21.0 (SD = 23.6), based on coding on the 100-point strength score from the WellSAT 3.0 [ 43 ], which is similar to the coding used in the current work. These findings highlight the importance of writing strong and comprehensive model policies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the original LWP mandate, there has been a patchwork of district LWPs and state laws governing the school wellness, health, nutrition, and physical activity environments in the United States [ 5 , 6 , 7 , 8 ]. There are tools for measuring the comprehensiveness (scope) and strength (required provisions) of LWPs [ 9 , 10 , 11 ] and concomitant state laws [ 11 , 12 , 13 , 14 ]. Numerous studies within individual states and nationwide have examined LWP content, consistently demonstrating that while LWPs are comprehensive (i.e., addressing many topics), they are often weak (i.e., simply encouraging rather than requiring specific actions) [ 5 , 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%